Evidence of the law : proving legal claims - Lawson, Gary, 1958- (Chicago : The University of Chicago Press, 2017)
How does one prove the law? If your neighbour breaks your window, the law regulates how you can show your claim to be true or false; but how do you prove that in breaking your window your neighbour has broken the law? American jurisprudence devotes an elaborate body of doctrine - and an equally elaborate body of accompanying scholarly commentary - to worrying about how to prove facts. It establishes rules for the admissibility of evidence, creates varying standards of proof and assigns burdens of proof that determine who wins or loses when the facts are unclear. This book brings these evidentiary principles for proving law out of the shadows so that they can be analysed, clarified and discussed.
Previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 17, 2017).
Keywords: Evidence (Law) -- United States; Evidence (Law) -- Philosophy; Law; United States of America, USA; Jurisprudence & general issues; Methods, theory & philosophy of law; Laws of specific jurisdictions & specific areas of law; Legal systems: general